Statewide implementation of a quality improvement initiative for reproductive, maternal, newborn and child health and nutritionin Bihar, India - Creanga, Andreea A; Srikantiah, Sridhar; Mahapatra, Tanmay; Das, Aritra; Sonthalia, Sunil; Moharana, Prabir Ranjan; Gore, Aboli; Daulatrao, Sanjiv; Durbha, Rohini; Kaul, Sunil; Galavotti, Christine; Laterra, Anne; et al. (Journal of global health, 2020)
CARE India designed and implemented a comprehensive, statewide quality improvement (QI) initiative to improve reproductive, maternal, newborn, and child health and nutrition (RMNCHN) services in public facilities in Bihar. We provide a description of this initiative and its key results during 2014-2017. We reviewed program documents to identify QI strategies employed and ascertain their coverage. We analysed data from: a) two public facility assessments to ascertain the availability of essential equipment and supplies and the distribution of human resources by facility level; b) a four-phase provider mentoring and training intervention covering 319 facilities to examine changes in emergency obstetric and newborn care (EmONC) practices; and c) four state-representative household surveys to explore changes in selected RMNCHN service utilisation by health sector. Associations of interest were ascertained using χ tests. Thirty-eight District Quality Assurance Committees and QI teams in 98% of facilities were formed to develop an implementation plan for the QI initiative and oversee its execution. QI strategies were to strengthen facilities' infrastructure; build the state's contracting, procurement, and inventory management capacities; rationalise human resources; improve providers' skills; and modernise data systems. Implementation led to facility infrastructure upgrades, improved clinical staff distribution, and higher availability of equipment and supplies over time, especially in higher-level facilities. Following the mentoring and training intervention in facilities offering both basic and comprehensive EmONC, performance of key practices (eg, adequate administration of uterotonics <1 minute after birth, initiation of skin-to-skin care <5 minutes after birth) improved significantly ( < 0.05). CARE India collected program data and assisted with modernising data systems for tracking human resources, supplies, and program progress statewide. Of women seeking antenatal care, the proportion obtaining key screenings (eg, weight, blood pressure measurements) in public facilities increased over time ( < 0.05). A 6-percentage point decline in home deliveries during 2016-2017 was accompanied by a higher increase of deliveries in public than private facilities (5- vs 1-percentage point; < 0.05). Substantial advances were made in improving RMNCHN service quality in Bihar. Continued improvement building on the established QI platform is expected and should be guided by data from now functional data systems.